2015
DOI: 10.1103/physrevb.92.144401
|View full text |Cite
|
Sign up to set email alerts
|

Zigzag antiferromagnetic quantum ground state in monoclinic honeycomb lattice antimonatesA3Ni2SbO6(A=<

Abstract: We present a comprehensive experimental and theoretical study of the electronic and magnetic properties of two quasi-two-dimensional (2D) honeycomb-lattice monoclinic compounds A 3 Ni 2 SbO 6 (A=Li, Na). Magnetic susceptibility and specific heat data are consistent with the onset of antiferromagnetic (AFM) long range order at low temperatures with Néel temperatures ~ 14 and 16 K for Li 3 Ni 2 SbO 6 and Na 3 Ni 2 SbO 6 , respectively. The effective magnetic moments of 4.3  B /f.u. (Li 3 Ni 2 SbO 6 ) and 4.4  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 81 publications
11
66
1
Order By: Relevance
“…S3). It is worth to mention that the spin-reorientation-type transitions have been reported recently for several related antimonates: for example, Na 3 Co 2 SbO 6 [61], Li 3 Ni 2 SbO 6 [63], Na 3 Ni 2 SbO 6 [76], Li 4 FeSbO 6 [67]. …”
Section: B Magnetic Susceptibility and Magnetizationmentioning
confidence: 77%
See 1 more Smart Citation
“…S3). It is worth to mention that the spin-reorientation-type transitions have been reported recently for several related antimonates: for example, Na 3 Co 2 SbO 6 [61], Li 3 Ni 2 SbO 6 [63], Na 3 Ni 2 SbO 6 [76], Li 4 FeSbO 6 [67]. …”
Section: B Magnetic Susceptibility and Magnetizationmentioning
confidence: 77%
“…1 It was found that similarly to related honeycomb lattice antimonates A 3 Ni 2 SbO 6 (A = Li, Na) [76] and the lowest total energy corresponds to the AFM zigzag state. It is important to mention that this type ordering has been recently evidenced for honeycomb-lattice delafossites Cu 3 Ni 2 SbO 6 and Cu 3 Co 2 SbO 6 as refined experimentally from low temperature neutron diffraction studies [40,41].…”
Section: E Band Structure Calculations and Analysis Of The Orbital Smentioning
confidence: 90%
“…The corresponding J 1 – J 2 – J 3 quantum model was described in previous studies, where J i corresponds to exchange interactions between an atom and its i th neighbor. Depending on the sign of J 1 and the sign and ratio of J 2 / J 1 and J 3 / J 1 , different nontrivial spin configurations could be realized such as “zigzag,” “stripe,” different spiral structures, etc …”
Section: Introductionmentioning
confidence: 99%
“…In the structure, one can distinguish well‐ordered magnetoactive layers with Ni and Te atoms isolated from each other by nonmagnetic Na‐contained layers (Figure ). The edge‐sharing NiO 6 octahedra form a honeycomb lattice, where the TeO 6 octahedron is located in the center of each “comb.” Due to such crystal structure, Na 2 Ni 2 TeO 6 could be attributed to a quasi‐2D system, for which the magnetic interaction between adjacent Ni 2 TeO 6 layers is much less than intralayer exchanges or nonexistent . It has to be noted that the replacement of the composition in A 2 M 2 TeO 6 has a direct influence on its magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11]. Static magnetisation was studied in magnetic fields up to 15 T by means of a home-built vibrating sample magnetometer (VSM) and in fields up to 5 T in a Quantum Design MPMS-XL5 SQUID magnetometer.…”
Section: Methodsmentioning
confidence: 99%